2020
DOI: 10.3389/fnhum.2020.578112
|View full text |Cite
|
Sign up to set email alerts
|

Musical Tension Associated With Violations of Hierarchical Structure

Abstract: Tension is one of the core principles of emotion evoked by music, linking objective musical events and subjective experience. The present study used continuous behavioral rating and electroencephalography (EEG) to investigate the dynamic process of tension generation and its underlying neurocognitive mechanisms; specifically, tension induced by structural violations at different music hierarchical levels. In the experiment, twenty-four musicians were required to rate felt tension continuously in real-time, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Therefore, no typical N5 component was found. The results of Sun et al 4 showed that N5 may be induced by tonal shift at phrase boundaries could because the materials were self-written chords sequences, and listeners might analyze the harmonic structure rather than the event structure. Our results proved that the cognitive mechanisms of tonal modulations within the harmonic structure and event structure were different.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, no typical N5 component was found. The results of Sun et al 4 showed that N5 may be induced by tonal shift at phrase boundaries could because the materials were self-written chords sequences, and listeners might analyze the harmonic structure rather than the event structure. Our results proved that the cognitive mechanisms of tonal modulations within the harmonic structure and event structure were different.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporated) and were exported in mid format. Using Cubase 5.1 software, the mid files were set at a constant velocity of 100 and were archived with a Yamaha piano timbre at a tempo of 100 beats per minute in .wav format, the same method as used by Sun et al 4 , 8 . Each sequence lasted 9.6 s, and the quaver rest at the end of the first phrase was 300 ms. All scores of the sequences used in the current study were presented in Supplementary Information .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations